2008
DOI: 10.1042/bj20080972
|View full text |Cite
|
Sign up to set email alerts
|

Palladacycles catalyse the oxidation of critical thiols of the mitochondrial membrane proteins and lead to mitochondrial permeabilization and cytochrome c release associated with apoptosis

Abstract: Permeabilization of the mitochondrial membrane has been extensively associated with necrotic and apoptotic cell death. Similarly to what had been previously observed for B16F10-Nex2 murine melanoma cells, PdC (palladacycle compounds) obtained from the reaction of dmpa (N,N-dimethyl-1-phenethylamine) with the dppe [1,2-ethanebis(diphenylphosphine)] were able to induce apoptosis in HTC (hepatoma, tissue culture) cells, presenting anticancer activity in vitro. To elucidate cell site-specific actions of dmpa:dppe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 46 publications
2
32
0
2
Order By: Relevance
“…C7a similarly induced activation of caspase 3 in HL-60 cells as well as activated caspases -8 and -9 (data not shown). Although DTT showed a partial toxicity to MT-2 cells, C7a -mediated cytotoxicity was abolished by DTT treatment in both cell lines (Figure 4C), suggesting that this cyclopalladated complex can induce thiol-cross-linking of mitochondrial membrane proteins resulting in mitochondrial permeabilization in leukemia cells, as previously described in murine melanoma cells treated with the R ( + ) enantiomer of C7a [12]. …”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…C7a similarly induced activation of caspase 3 in HL-60 cells as well as activated caspases -8 and -9 (data not shown). Although DTT showed a partial toxicity to MT-2 cells, C7a -mediated cytotoxicity was abolished by DTT treatment in both cell lines (Figure 4C), suggesting that this cyclopalladated complex can induce thiol-cross-linking of mitochondrial membrane proteins resulting in mitochondrial permeabilization in leukemia cells, as previously described in murine melanoma cells treated with the R ( + ) enantiomer of C7a [12]. …”
Section: Resultssupporting
confidence: 73%
“…However clinical use of arsenic is problematic as there are differences in sensitivity to As 2 O 3 , and arsenic itself is toxic at high doses [13]. C7a and the R ( + ) enantiomer complex have been described as potent inducers of apoptosis through targeting of the mitochondria by interacting with thiol-groups in the mitochondrial membrane of murine melanoma cells [10], and in rat isolated mitochondria [12], respectively. Treatment of isolated rat liver mitochondria with the R ( + ) enantiomer of C7a, {Pd 2 [ R ( + ) C 2 , N-dmpa] 2 (μ-dppe)Cl 2 } results in mitochondrial permeabilization as indicated by Ca +2 - and ROS-independent mitochondrial swelling, release of cytochrome c , dissipation of the mitochondrial transmembrane potential, uncoupling of oxidative phosphorylation, and mitochondrial calcium release [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] demonstrated that an enantiomer of cyclopalladated C7a {Pd 2 [ R (+) C 2 , N-dmpa] 2 (μ-dppe)Cl 2 } interacts with thiol groups of the membrane proteins from rat liver isolated mitochondria, promoting specific protein thiol cross-linkage, inducing mitochondrial permeabilization and cytochrome c release. This effect was abolished by preincubation of isolated mitochondria with DTT, a thiol reducing agent.…”
Section: Resultsmentioning
confidence: 99%
“…One of these compounds, called complex 7a, showed specific in vitro and in vivo activities against tumor cells, with no significant toxicity in animals, even at high doses (20). The 7a compound causes anoikis and apoptosis of tumor cells (F. A. Serrano, D. C. Arruda, A. L. Matsuo, L. S. Silva, S. Smaili, A. C. F. Caires, L. R. Travassos, and E. G. Rodrigues, unpublished data), and its enantiomer is able to oxidize mitochondrial proteins leading to permeabilization and cytochrome c release (21).…”
mentioning
confidence: 99%